Successful Treatment of AA Amyloidosis in Ankylosing Spondylitis Using Tocilizumab: Report of Two Cases and Review of the Literature - Eriksson, Per; Mölne, Johan; Wirestam, Lina; Sjöwall, Christopher (Frontiers in Medicine, 2021)
Historically, secondary amyloidosis has been a feared complication of chronic inflammatory conditions. The fibril protein AA derives from the acute phase reactant serum amyloid A (SAA). Long-term elevation of SAA levels remains a major risk factor for the development of AA amyloidosis in rheumatic diseases, and the prognosis may be unpredictable. Nowadays, with increased availability of effective biological agents, the incidence of AA amyloidosis seems to be declining. Still, genetically predisposed subjects with slowly progressive disease and mild symptoms combined with ongoing systemic inflammation may be at risk. Interleukin-6 (IL-6) is one of the drivers of SAA release and effectiveness of the humanized anti-IL-6 receptor antibody tocilizumab (TCZ) for the treatment of AA amyloidosis has been observed in some rheumatic conditions. Herein, we report two male subjects with longstanding ankylosing spondylitis (AS) complicated by renal amyloidosis who received TCZ with rapid and beneficial effects regarding inflammation and proteinuria. To the best of our knowledge, the use of TCZ in AS patients with this extra-articular manifestation has not previously been described. The paper includes histopathology, clinical follow-up and longitudinal data of the two cases along with a comprehensive review of relevant literature. Mechanisms behind amyloid-mediated tissue damage and organ dysfunction are discussed. Altogether, our data highlight that blocking IL-6 signaling may represent a promising therapeutic option in patients with renal AA amyloidosis.